Multifactor Authentication for Enhanced Accesss Control Security for Websites - Hassoun, Mohammed M. (2010)
Nowadays, computer security becomes a major issue for users and developers. Security experts and developers are working together to bridge the security gaps by the realistic diagnosis of threats. They try to find the best ways to apply reasonable solutions in regard to cost, time, and usability. The issue of security has become one of the Common Era concerns. Users are divided into two groups, firstly, computer users, secondly, internet users (website users). Website's users do not like to buy expensive or sophisticated devices, and they just want to access their data in the safety way possible. This research sheds light upon enhancing the access control of websites by employing mobile phone and email features to serve this purpose. The system using the ordinary username and password for user login, and the PassCode. It is generated for every login request. This PassCode has a special scenario, firstly, using email to send the encrypted PassCode to the user, secondly decrypt the PassCode before use it to login by an application installed on the user's mobile phone. Moreover, there are other features added to the system expired of password and Bluetooth device address of the mobile phone. The latter is used as identification to the user, to reach a high level of confidentiality.